1992
DOI: 10.1101/gad.6.6.975
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of murine ets-1 with GGA-binding sites establishes the ETS domain as a new DNA-binding motif.

Abstract: The proto-oncogene ets-1 is the founding member of a new family of eukaryotic transcriptional regulators. Using deletion mutants of murine ets-1 cDNA expressed in Escherichia coli, we show that the DNA-binding domain corresponds closely to the ETS domain, an 85-amino-acid region that is conserved among ets family members. To investigate the specificity of DNA binding of the ETS domain, we mapped the DNA contacts of a monomeric Ets-1 fragment by chemical protection and interference assays. DNA backbone interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
330
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(351 citation statements)
references
References 51 publications
21
330
0
Order By: Relevance
“…rEts1 bound to EBS2 and EBS4 but failed to bind to EBS1, EBS3 or EBS5, although they had the correct GGAA/T core sequence. These results support the previous observations that an A in position 73 relative to the ®rst G of the core sequence and a G in position +5 favor binding of Ets1 to DNA (Fisher et al, 1991;Nye et al, 1992;Woods et al, 1992).…”
Section: Discussionsupporting
confidence: 91%
“…rEts1 bound to EBS2 and EBS4 but failed to bind to EBS1, EBS3 or EBS5, although they had the correct GGAA/T core sequence. These results support the previous observations that an A in position 73 relative to the ®rst G of the core sequence and a G in position +5 favor binding of Ets1 to DNA (Fisher et al, 1991;Nye et al, 1992;Woods et al, 1992).…”
Section: Discussionsupporting
confidence: 91%
“…Elf5 bound the E74 oligonucleotide (containing a GGAA-core) (lane 1), but not to the E74m1 oligonucleotide (which had been mutated to an AGAA-core) (lane 2). The ®rst G-residue of the core has been demonstrated to be a physical point of DNA contact for ETS1, and consequently essential for DNA binding (Fisher et al, 1991;Nye et al, 1992). Thus, Elf5 displays sequence speci®c binding to a consensus ETS binding site, binding that is disrupted by a mutation known to similarly a ect other ETS family members.…”
Section: Sequence-speci®c Binding Of Elf5 To Dna Sequences Containingmentioning
confidence: 99%
“…Hybridizations were carried out as previously described (Kinzler et al, 1988) as monomers (Wasylyk et al, 1993). While the ETS domain has been extensively characterized as a modular domain that mediates binding to the core DNA consensus motif GGAA/T (Nye et al, 1992;Seth et al, 1992), a number of recent studies with ETS family proteins have shown that this domain may also mediate distinct functions such as interactions with heterologous proteins (Treisman, 1994), associations with other ETS proteins (Carrere et al, 1998), and even RNA binding activity (Hallier et al, 1996). Thus, it is possible that the ETS domain may mediate critical protein-protein interactions, independently of DNA binding activity, that are required for transformation by EWS/FLI.…”
mentioning
confidence: 99%